Infrações e sanções administrativas aplicáveis aos particulares em licitações e contratos - Puccetti, Renata Fiori (2010)
The paper concerns an investigation of the legal regime of infractions and penalties applicable to private agents in the subject-matter of public tenders and administrative contracts, and address questions related that comprise the analysis of the infractions and sanctions in species, existent in the Brazilian legal system, the presuppositions and procedures to the verification and sanctioning, as well as acquaint their aspects and extension. Are types of special relationship of submission, characterized by the bond of differentiated approximation, what entails to acknowledge its differentiated legal regime from ordinary relationship of submission, within the sanctioning administrative law